Child Rearing Styles of Queer Parents in Relation to Child Adjustments - Fernandez, Christine Joy L.; Ayro, Eufemia C.; Mamaclay, Ali G.; Cruz-Vidal, Michaela Jennarine DL.; Pangan, Emmanuel John R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study focused on determining the child rearing styles of queer parents about child adjustment. The case study was used to determine the unique experiences of the subject participants. Eight queer parents and eight children of queer parents participated in the study. Further, the researcher used unstructured interviews in collecting the research data. The results revealed that most of the queer parents belonged within the age range of more than 40, gay men and lesbian women, unmarried and living with no partner, Roman Catholic, Ilokano and Tagalog, college graduate, self-employed with a monthly family income of 20,001 – 30,000, and with one child. Moreover, most of the male and female child participants were under 17, first-born child with one sibling belonged to household members of three, nephews of queer parents and lived with their non-biological parents for more than 14 years. There is an emerging theme derived from the experiences of queer parents, such as their experiences in various aspects of parenthood. The queer parents’ child rearing styles were lax parenting style and disciplinarian style. Two emerging themes derived from the participants' experiences, such as their lived experiences consisting of three sub-themes: being raised by non-biological parents, being bullied and having conflict with parents. Similarly, two sub-themes were derived from the theme description of the present life, such as comfortable life and crossing to life challenges. The child adjustment that emerged was psychosocial. The emerging well-being of the child participants was life contentment. The emerging sub-themes under the description of parents’ way of rearing a child were composed of imposition of discipline, provision of basic needs and inculcation of the value of education. The child participants were appreciative and satisfied with the kind of life they had. Since most of the parents were single, the government through the local government units may properly disseminate the Solo Parent Act as to benefits and privileges under the law through series of orientation and assist the queer parents to have their Solo Parents card. Non-government organization, civic organization and the church may conduct series of guidance and counselling, psychological intervention and spiritual nurturing programs and activities to enhance the quality of life among child of the queer parents.